2022
DOI: 10.3390/polym14040731
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Sodium Alginate—Locust Bean Gum Films Reinforced with Daphnetin Emulsions for the Development of Active Packaging

Abstract: In this study, we characterized an active film made of sodium alginate (SA)—locust bean gum (LBG) containing daphnetin-based film. Physicochemical characteristics, as well as antioxidant and antibacterial properties, were investigated. The results showed that the addition of a low concentration of daphnetin increased the flexibility of SA–LBG cling film, leading to an improvement in elongation at break and tensile strength. As the daphnetin content increased, solubility, brightness and transparency of the clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…It is a preferred material for making green packaging for food due to its long polymer chain, safety, nontoxicity and easy availability [ 43 ]. Hao Cheng et al [ 44 ] prepared a sodium alginate-sophora bean gum active film containing ryanodine and measured its physical, antioxidant and antibacterial properties. The results showed that the appropriate amount of daphnetin could improve the optical, mechanical and barrier properties of the active film, and the antioxidant and antibacterial properties of the active film were enhanced with the increase of the daphnetin content.…”
Section: Types Of Bio-based Materialsmentioning
confidence: 99%
“…It is a preferred material for making green packaging for food due to its long polymer chain, safety, nontoxicity and easy availability [ 43 ]. Hao Cheng et al [ 44 ] prepared a sodium alginate-sophora bean gum active film containing ryanodine and measured its physical, antioxidant and antibacterial properties. The results showed that the appropriate amount of daphnetin could improve the optical, mechanical and barrier properties of the active film, and the antioxidant and antibacterial properties of the active film were enhanced with the increase of the daphnetin content.…”
Section: Types Of Bio-based Materialsmentioning
confidence: 99%
“…DAP as an emulsion [locus bean gum (0.5%) and sodium alginate (1.5%)] is used in the food industry as an additive, preservative and packaging material. It is used as a preservative because of antimicrobial and antioxidant properties ( Liu et al, 2021 ; Cheng, 2022 ).…”
Section: Pharmacological Activities Of Daphnetinmentioning
confidence: 99%
“…Indeed, a systematic study in the presence of raw GPWW is absent in the literature when referring to SA-based films for food packaging. Only a few examples are reported and devoted to the use of polyphenols derived from plants but not concerning water-resistant SA films [29,[32][33][34][35]. Therefore, the characterization and the application of water-resistant SA-based films derived from grape wastes (SA + GPWW) are proposed during this work, demonstrating their stability and properties under different work conditions.…”
Section: Introductionmentioning
confidence: 99%